Implementasi Transformasi Digital Dalam Pelayanan Publik Melalui Website Pemerintah Daerah Pada Dinas Komunikasi Dan Informatika Kabupaten Dompu - Fena Fentika; Rossi Maunofa Widayat; M Ariy Dermawan; Muhammad Ali (Jurnal Administrasi Publik dan Pemerintahan, 2026)
The implementation of the Dompu Regency Government website is one of the strategic efforts in encouraging digital transformation and improving the quality of electronic-based public services. However, its implementation still faces various obstacles such as limited utilization by several regional apparatus organizations that use the Dompukab.go.id domain, still at 30% of the ideal target of 100% and 70% of other regional apparatus organizations have not fully utilized the use of official subdomains optimally, uneven network infrastructure, and low digital literacy of the community, especially in blank spot areas, also hamper its implementation. This study aims to analyze the implementation of the Dompu Regional Government website as a form of digital transformation that previously shifted from conventional services in the form of Simolin cars based on six indicators of Munoz and Bolivar (2018), namely Strategic E-Government Plan, Technologies Used, Technological Issues, Policies and Programs, Digital Divide–Citizens’ Acceptance, and Legal and Policy Barriers. Using a descriptive qualitative approach, data was obtained through interviews, observations, and documentation with key informants from the Dompu Regency Communication and Informatics Office and community service users. The research results indicate that the implementation of the local government website has a strong policy foundation, structured program support, and adequate technological readiness. In conclusion, the Dompu local government website has served as an important instrument in providing information services, but its effectiveness requires strengthening human resource capacity, equitable digital access, and optimizing website utilization by all regional government organizations.